Effect of Interleukin and Hepcidin in Anemia of Chronic Diseases - Maha F. Yacoub; Hala Fouad Ferwiz; Fadwa Said (Anemia)
Background. Anemia of chronic disease (ACD) also termed as the anemia of inflammation has been found to be associated with inflammations, chronic infections, and cancers, particularly in old age. Recent studies revealed that interleukin-6 (IL-6), a proinflammatory cytokine, and hepcidin, an antimicrobial hepatic peptide, play a key role in ACD pathogenesis. Patients and Methods. The study included 40 subjects with chronic diseases and 40 normal subjects of the same age group. Red cell indices, levels of IL-6 and hepcidin, and iron profile were measured in all participants using Bayer ADVIA 120, VITROS 5600, Integrated System/2008, and ELISA assay, respectively. Results. The level of hemoglobin was considerably less in patients of chronic diseases referred to as “cases” than the normal subjects or “controls” (8.7 ± 1.5 vs. 13.2 ± 0.9). Red blood corpuscle (RBC) count, hematocrit (HCT) level, serum iron, mean corpuscular hemoglobin concentration (MCHC), and serum total iron-binding capacity (TIBC) were found to be significantly lower in the cases as compared to controls (p<0.001). Serum IL-6 and hepcidin levels were substantially higher in the cases than in the controls (p<0.001 and p<0.02, respectively). Conclusion. This study detected a significant increase in serum IL-6 and hepcidin levels in patients with ACD than the controls. These findings offer an insight into the role played by both cytokine and peptide in the pathogenesis of ACD and thus provide a rationale for future use of novel drugs inhibiting their effects on iron metabolism.